APPLYING NEGOTIATION PROCESS – THEORETICAL AND PRACTICAL UNDERSTANDINGS (Security Dialogues, 2025)
There is no doubt that conflicts (violent or non-violent) are an integral part of therelations between different actors at both, the national, regional and international levels.Starting from this conclusion, there is an inevitable need for applying appropriate strategiesand approaches that will enable their efficient and successful management and resolution.It is exactly from such aspect that the significance of the negotiation process arises as aninstrument for peaceful resolution of open issues or disputes, through the establishment andrealization of communication between the opposing parties. However, as the experience todate in this regard shows, the realization of the negotiation process is not always establishedand realized in accordance with the projected visions. Hence, the focus of this paper isspecifically directed towards the analysis of the negotiation process essence, mainly throughthe prism of some of the existing theoretical and practical aspects in this regard. Specifically,by analyzing the characteristics of the basic elements, phases and models of the negotiationprocess, the aim is closer identification of the main challenges and perspectives related tothe applicability of the negotiation process.